Alternations in the chain length distribution of polysaccharides by adjusting the active sites of the 1, 4-α-glucan branching enzyme. (December 2022) - Ban, Xiaofeng; Wang, Tao; Jiang, Haimin; Li, Caiming; Gu, Zhengbiao; Cheng, Li; Hong, Yan; Li, Zhaofeng
Graphical abstract: Highlights: Manipulation of Gln 489 in branching enzyme changes structure of polysaccharide. Substitution Gln 489 with Gly results in highly branched polysaccharide. Substitution Gln 489 with Arg increases branching activity of branching enzyme. Abstract: The 1, 4-α-glucan branching enzymes (GBEs, EC 2.4.1.18) catalyze the formation of new α-1, 6 branching points in starch, playing an irreplaceable role in controlling the frequency and position of branch points in glucan chains, which present several potential applications in starch industry. Previously, a thermostable GBE that originates from Rhodothermus obamensis STB05 (RoGBE) is reported to be an excellent glycosyltransferase to modify the structures of starch. However, until now, how to control the length of the transferred glucan chains is still a challenge. Structural analysis of RoGBE shows that the residue at amino acid site 489 connects with the reducing end of the substrate, which may determine the chain length of binding oligosaccharides. The substitutions of Gln at this site with Arg, Glu and Gly result in alternations at catalytic activities and transglycosylation patterns of GBE. Specifically, the Q489E, and Q489R mutants had 5–10 % increases in catalytic activities, the Q489G shows that a slight decrease in activity. versus modified maltodextrin with wild-type RoGBE, maltodextrin incubated with Q489G, Q489E, and Q489R mutants show a 4.17 %–22.43 % increase in the ratio of glucan chains with DP < 13 in the oligosaccharide chains of modified maltodextrin. Crystallographic analyses and simulations were performed to reveal the structural alternations mediated by the introduced mutations. These results are important in the context of understanding the mechanism of action of the thermostable glycosyltransferase and can help develop more functional glycosyltransferases for controlling the glucan chains of polysaccharides.